IMPLEMENTASI KEBIJAKAN PENERAPAN ELEKTRONIK VOTING (E-VOTING) DALAM PEMILIHAN KEPALA DESA (Studi Kasus : Pemilihan Kepala Desa di Desa Mendoyo Dangin Tukad, Kecamatan Mendoyo Kabupaten Jembrana) - Anistiawati, Made Leita (CITIZEN CHARTER, 2014)
Abstract Village elections is usually done by voting, perforate or ticking. In conventional elections that loaded with fraud will make the low level of public trust to government. Evoting usage in avillage election is a new way from government in provide service to the community. The purpose of this study is to investigate the implementation of village elections with e-voting system. This research use deskrptive qualitative method conduct interview with informants and doing obsaervation in the field with the result that the research obtain data needed in the research study. These results indicate that the implementation of policies in the rural village elections Mendoyo Dangin Tukad with e-Voting system is abel to achieve the four principles of good government. The principles embodied colorable, ie the principles of accountability, participation, transparency, effective and efficient. On the principle of accountability implementations of the e-voting system cen be audited. The principle of transparency in village elections in rural Mendoyo Dangin Tukad views can be seen from the results of the vote, whilw in the most effective and efficient visible from the voting, e-voting system witt voter only takes an average of 20 seconds. In terns of financing of e-voting in the village Mendoyo Dangin TukadÂ  only spent a total of 8.700.000 is very different to a considerable cost. The last principle is reflected in the implementation of e-voting is participation. E-voting system is able to restore public confidence in the government in holding elections. Keywords : village elections, e-voting, good governance.